Объяснение:
1) NaOH + HCl = NaCl + H2O
Na(+)+ OH(-)+ H(+) + Cl(-) = Na(+) + Cl(-) + H2O
H(+) + OH(-) = H2O
2) MgCl2 + Na2SO3 = MgSO3 + 2NaCl
Mg(2+) + 2Cl(-)+ 2Na(+) + SO3(2-) = MgSO3 + 2Na(+) + 2Cl(-)
Mg(2+) + SO3(2-) = MgSO3
3) K2SO3 + 2HNO3 = 2KNO3 + SO2 + H2O
2K(+) + SO3(2-) + 2H(+) + 2NO3(-) = 2K(+) + 2NO3(-) + SO2 + H2O
SO3(2-)+ 2H(+) = SO2 + H2O
4) ZnSO4 + 2NaOH = Zn(OH)2 + Na2SO4
Zn(2+) + SO4(2-) + 2Na(+) + 2OH(-)= Zn(OH)2 + 2Na(+)+ SO4(2-)
Zn(2+)+ 2OH(-) = Zn(OH)2
5) Al(OH)3 + 3HNO3 = Al(NO3)3 + 3H2O
Al(OH)3 + 3H(+)+ 3NO3(-) = Al(3+) + 3NO3(-)+ 3H2O
Al(OH)3 + 3H(+) = Al(3+) + 3H2O
6) CaCO3 + 2HCl = CaCl2 + CO2 + H2O
CaCO3 + 2H(+) + 2Cl(-)=Ca(2+) + 2Cl(-) + CO2 + H2O
CaCO3 + 2H(+) = Ca(2+) + CO2 + H2O
Объяснение:
1) NaOH + HCl = NaCl + H2O
Na(+)+ OH(-)+ H(+) + Cl(-) = Na(+) + Cl(-) + H2O
H(+) + OH(-) = H2O
2) MgCl2 + Na2SO3 = MgSO3 + 2NaCl
Mg(2+) + 2Cl(-)+ 2Na(+) + SO3(2-) = MgSO3 + 2Na(+) + 2Cl(-)
Mg(2+) + SO3(2-) = MgSO3
3) K2SO3 + 2HNO3 = 2KNO3 + SO2 + H2O
2K(+) + SO3(2-) + 2H(+) + 2NO3(-) = 2K(+) + 2NO3(-) + SO2 + H2O
SO3(2-)+ 2H(+) = SO2 + H2O
4) ZnSO4 + 2NaOH = Zn(OH)2 + Na2SO4
Zn(2+) + SO4(2-) + 2Na(+) + 2OH(-)= Zn(OH)2 + 2Na(+)+ SO4(2-)
Zn(2+)+ 2OH(-) = Zn(OH)2
5) Al(OH)3 + 3HNO3 = Al(NO3)3 + 3H2O
Al(OH)3 + 3H(+)+ 3NO3(-) = Al(3+) + 3NO3(-)+ 3H2O
Al(OH)3 + 3H(+) = Al(3+) + 3H2O
6) CaCO3 + 2HCl = CaCl2 + CO2 + H2O
CaCO3 + 2H(+) + 2Cl(-)=Ca(2+) + 2Cl(-) + CO2 + H2O
CaCO3 + 2H(+) = Ca(2+) + CO2 + H2O